Social Media Memes in Pakistan: An Exploratory Study on Contents of Memes - Ayesha Niazi, (Journal of Peace, Development and Communication, 2024)
Memes have become a progressively common form of visual communication in past years, which has recently grabbed significant research interest. This study was conducted to explore the types/categories of memes and the way memes contents were presented on social media. The researcher did a content analysis and generated a coding sheet of fifty memes, twenty-five from Twitter and twenty-five from Instagram, and found that memes were classified as (informational, educational, political, promotional, religious, social, and cultural) memes categorized under seven major themes (awareness, factual, humiliating, humorous, roasting, serious, and trolling) according to their nature and content presentation. It is explored that most of the memes in a political category are serious and trolling in nature but in social/cultural categories, memes are used as humorous and humiliating in nature. On the other hand, five major themes emerged according to the coding sheet, these are (verbal language, attire, environment, personification attribute, and non-verbal language). The results show that in the present study, more memes are found in the English quality language and several memes in the Urdu slang language are greater while national attire is more leading in memes and they are more made in a domestic environment. Under the category of personification attribute, real-time characters and entertainment-based celebrities are highly highlighted in memes, and within the category of non-verbal language, the researcher derived thirty major themes based on the content of social media. According to this analysis, the political aspects category is more found in body language analysis of the contents of memes which shows that most of our memes are related to political characters and issues. The concept of code-mixing from English to Urdu and Urdu to English has also been observed.